Compensation Of Educational Personnel Moderates The Influence Of Academic Information System Service Quality On Student Satisfaction - Ari Usman Efendi; Deviyantoro Deviyantoro (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to determine compensation moderating the influence of service quality of educational staff on student satisfaction at Serang Raya University. The form of research used is descriptive and quantitative research. Descriptive research is a form of research that aims to describe existing phenomena, both natural phenomena and man-made phenomena. The population in this study were 100 educational staff respondents and 100 student respondents at Serang Raya University. Then, data processing used the SmartPLS 4.0 application. The results showed that the interaction of compensation variables had a positive but insignificant effect on service quality of 0.184 with a p-value of 0.063 (> 0.05 ) . The interaction of service quality variables had a significant positive effect on student satisfaction of 0.915 with a p- value of 0.000 (<0.05) and the interaction of compensation variables in moderating service quality on student satisfaction had a positive but insignificant effect of 0.048 with a p-value of 0.373 (> 0.05). The study was conducted at only one institution (University of Serang Raya), so the findings may not be generalizable to other organizations. The findings of this study have the potential to lead to the development of a new theoretical framework that incorporates the moderating effect of compensation on the relationship between service quality and student satisfaction. This framework can provide a more comprehensive understanding of how compensation affects student satisfaction in educational settings.